Development of e-worksheets using Canva-Heyzine flipbook on excretory system material for eleventh graders - Afreni Hamidah; Putri Setia Asni Ningrum; Raissa Mataniari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
This study aims to develop e-worksheet teaching materials on the excretory system, assess their feasibility, analyze teacher responses, and evaluate trial results using the e-worksheet. The research follows a Research and Development (R&D) approach, employing the ADDIE development model. The study was conducted at SMAN 8 Tanjung Jabung Timur, involving two biology teachers and class XI IPA students, divided into small groups (6 students) and large groups (27 students). Both qualitative and quantitative data were collected using questionnaires. The validation results indicate that the material experts rated the e-worksheet at 91.25% ("Very Good"), while media experts gave a rating of 87.5% ("Very Good"). The biology teachers’ perceptions also yielded a 91.25% ("Very Good") rating. In the small group trial, students provided a total score of 452, equivalent to 94% ("Very Good"). In the large group trial, the total student assessment score reached 1,879, with a percentage of 87% ("Very Good"). Overall, the study demonstrates that the e-worksheet is feasible for use in learning, as validated by subject matter and media experts. Additionally, it is considered practical by teachers and students, effectively enhancing motivation, engagement, and understanding of the excretory system. Therefore, the e-worksheet serves as a valuable alternative solution to existing learning challenges in biology education.